The communication in humanistic organizations. Reflections from university management (Gestión y Gerencia, 2025)
This essay presents a traditional approach, focused on the transmission of knowledge versus the humanistic approach, which prioritizes dialogue and human interaction, as one of the pillars introduced by transmodernity, aimed at contributing to the debate and revealing answers regarding communication in universities as humanistic entities with systemic behavior, as they are made up of people among whom relationships arise naturally and are indispensable to their functioning. Communication is assumed to be a basic and conditioning process in the human entity, of worldviews, obstacles, and opportunities. Therefore, during the actions aimed at consolidating the objectives set, it is necessary to additionally consider the existential requirements as social beings. This is a hermeneutic-documentary study, under the interpretive paradigm, which sought to characterize communication in universities from a humanistic perspective.
Keywords: Communication; humanistic organization; management; university